Theoretical aspects of computing - ICTAC 2015 : 12th International Colloquium, Cali, Colombia, October 29-31, 2015, proceedings /: 12th International Colloquium, Cali, Colombia, October 29-31, 2015, proceedings. (2015) - Unknown
No abstract available